Post-Conflict Political Mobilization and Borderland Brokers in Madhesh: A Case Study of Saptari, Nepal - Karn, Sujeet (Nepal Journal of Sociology, 2025)
Based on the extensive fieldwork carried out in the southern plains of Nepal, this paper, juxtaposes Nepal’s post- conflict transition by framing the political events that fanned out after 2007, the reverberations affecting the dynamics of evolving center-periphery relations, and the emergence and resurgence of borderland brokers, who functioned as intermediaries in shaping the agenda of Madhesh and negotiating with Kathmandu. In doing so, the paper focuses on the provincial town of Saptari, located in the southern Tarai borderland, as a case study. By grounding the conceptual framework of brokers and brokerage, the paper showcases the connection between post-conflict peacebuilding and the role of borderland brokers. It argues that the margins of the state are crucial for understanding the dynamics of post-conflict scenarios and the power relations that prevail at the national level. This argument is further substantiated by charting three distinct individual trajectories of borderland brokers, which elucidate their strategies, networks and personalities within both local and national political domains.